A rare case of primary fallopian tube carcinoma in a woman with post-menopausal bleeding - Paul, P. G.; Annal, Anjana; Chowdary, K. Anusha; Shilotri, Manali; Paul, George; Degapudi, Madhumathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Primary fallopian tube carcinoma (PFTC) is a rare tumor accounting for about 0.5% of all gynecological cancers. The rarity of the tumor with its non-specific clinical presentation and radiological findings lead to a low suspicion of PFTC by the attending clinician. We present a case of this tumor in a 62 years post-menopausal parous woman who presented with intermittent vaginal bleeding with normal clinical examination and an adnexal mass on USG and MRI. She underwent laparosopic total hysterectomy with bilateral salpingo-oophorectomy, infracolic omentectomy and staging biopsies followed by adjuvant chemotherapy. Primary fallopian tube carcinoma should be considered in the differential diagnosis of peri and postmenopausal women who present with an adnexal mass, unexplained bleeding per vaginum, pelvic pain, or a cervical smear with abnormal glandular cells. The treatment is similar to epithelial ovarian carcinoma, which includes total hysterectomy with bilateral salpingo-oophorectomy and comprehensive surgical staging.